Влияние возраста, стажа и продолжительности работы за компьютером на реологические свойства крови пользователей - Максюта, Наталия Валерьевна; Будянская, Э. Н.; Снурников, М. Я.; Чернобровкина, Т. В. (НТУ "ХПИ", 2008)
Обсуждается проблема отрицательного влияния работы за компьютером на здоровье пользователей. Показана роль своевременного выявления и коррекции нарушений реологических свойств крови. С помощью дисперсионного анализа, критериев Стьюдента и Хоттеллинга на примере мужчин выполнен сравнительный анализ влияния возраста, времени и стажа работы за компьютером на состояние реологических свойств крови.

The problem of negative influence of work behind a computer on users health is discussed. The role of duly revealing and correction of infringements reology blood properties is shown. By means of the dispersive analysis, t-criteria and criteria Hotelling’s on an example of men the comparative analysis of influence of age, time and the experience of work behind a computer on a condition reology blood properties is executed.
Influence of age, the experience and operation time behind a computer on reology blood properties of users
Keywords: компьютерная техника; здоровье пользователей; неблагоприятные факторы; сравнительный анализ; health of occupants; reologic properties of blood; comparative analysis